2019
DOI: 10.1007/s00402-019-03270-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overscreening hip fracture patients

Abstract: Background The aim of this study was to prospectively investigate the adherence to the American College of Cardiology (ACC) and the American Heart Association guidelines for perioperative assessment of patients with hip fracture in daily clinical practice and how this might affect outcome. Methods This prospective cohort study from Maastricht University Medical Centre included 166 hip fracture patients within a 3-year inclusion period. The preoperative cardiac screening and adherence to the ACC/AHA guideline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Smeets et al. examined the adherence to these guidelines in a prospective cohort study [ 14 ]. They found that 87% of patients received the correct screening, with “overscreening” being the predominant reason for incorrect screening [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smeets et al. examined the adherence to these guidelines in a prospective cohort study [ 14 ]. They found that 87% of patients received the correct screening, with “overscreening” being the predominant reason for incorrect screening [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…examined the adherence to these guidelines in a prospective cohort study [ 14 ]. They found that 87% of patients received the correct screening, with “overscreening” being the predominant reason for incorrect screening [ 14 ]. A larger retrospective study found that only 29% of the patients with cardiac consultations met the guidelines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors affect the mortality, some of those are time to start-of-surgery [2], cementation of hemi-or total arthroplasty [3], and preoperative morbidity assessed by American Society of Anaesthesiologist (ASA) risk score and Nottingham Hip Fracture Score (NHFS) [4,5]. Preoperative cardiology consulting, however, rarely affects surgical management, but could alter anesthesiologic management [6].…”
Section: Researchmentioning
confidence: 99%
“…6,7 Preoperative cardiology consulting, however, rarely affects surgical management, but could alter anesthesiologic management. 8 The peri-operative anaesthesia strategy for the management of the frail hip fracture patient differs worldwide: where many centers give general anaesthesia, while particularly in northern Europe, neuraxial anaesthesia is the preferred technique. However, both techniques frequently induce hypotension, requiring fluid resuscitation and/or the need for vasopressors.…”
Section: Introductionmentioning
confidence: 99%